Knowledge, attitude, and practice of physicians regarding pain management in patients with Sickle cell disease - Ismail, Abdellatif; Aqel, Ali; Abumuhfouz, Ma’in; Safieh, Mohamad; Arabyat, Mahmoud; Ibrahim, Mohamed; Singh, Kalpana; Yassin, Mohamed A. (Frontiers in Hematology, 2023)
Sickle cell disease (SCD) is a hemoglobin disorder inherited in an autosomal recessive pattern. Pain from vaso-occlusive crises (VOCs) is the most common symptom experienced by patients with SCD; thus, pain management constitutes a significant role in this patient population. We hypothesize that physicians with less favorable attitudes toward SCD patients are less likely to follow pain management guidelines. In this cross-sectional convenience sample survey, we aim to assess the adherence of physicians in our institute to guidelines for the management of SCD pain crisis and study the factors that are associated with non-adherence to these guidelines. Most surveyed physicians were in an early-career status and were found to adhere to the recommendations of using opioids and NSAIDs as first-line therapy and avoiding using meperidine. On the other hand, some analgesic practices deviated from the recommendations, including less frequent assessment and reassessment of pain and response to pain medications and less frequent use of opioid patient-controlled analgesia (PCA). We conclude that the physicians taking care of SCD patients in our institute adhere to some of the guidelines in the field more than others. We also conclude that they have negative attitudes toward SCD patients; nevertheless, these did not affect their pain management practices.